S100A8/A9 inhibition reduces splenic myelopoiesis and improves outcomes after stroke - Kim, Hyun Ah; Al-sharea, Annas; Chu, Hannah X.; Tang, Sung-Chun; Rupasinghe, Samoda A.; Zhang, Shenpeng R.; Nagareddy, Prabhakara R.; Drummond, Grant R.; Arumugam, Thiruma V.; Murphy, Andrew J.; Sobey, Christopher G.; Lee, Man K.S. (Frontiers in Immunology, 2026)
IntroductionNeutrophils are among the earliest immune cells to infiltrate the ischemic brain and contribute to secondary neuronal damage. The alarmin S100 calcium-binding protein A8/A9 (S100A8/A9), predominantly released by neutrophils, is upregulated during this process. Although the bone marrow is recognized as the principal site of neutrophil production via myelopoiesis, the role of the spleen as an immune-responsive organ remains incompletely understood.MethodsIn this study, we employed a transient middle cerebral artery occlusion model in male C57Bl/6 mice and examined immune responses 24 hours post-stroke in the blood, bone marrow and spleen using flow cytometry. To understand the role of S100A8/A9 in modulating stroke-induced myelopoiesis, we administered a small molecule inhibitor of S100A8/A9, ABR-215757, before and after stroke. Human brain was examined immunohistochemically.ResultsAnalysis of human brain tissue (4 stroke patients, 2 controls) indicated the presence of neutrophils and S100A8/A9 in infarcted regions. Interestingly, we observed a marked increase in splenic neutrophils, accompanied by an expansion of myeloid progenitors, indicating activation of extramedullary myelopoiesis. Given our previous work showing that S100A8/A9 promotes myelopoiesis, we pharmacologically inhibited S100A8/A9 to determine if this would modulate stroke-induced myelopoiesis. Treatment with ABR-215757 led to reduced splenic myelopoiesis, reversed neutrophilia, enhanced forelimb grip strength, and a one-third reduction in infarct size at 24 hours post-stroke.ConclusionThese findings identify the spleen as a key contributor to neutrophil production following stroke and suggest that targeting S100A8/A9 may mitigate myeloid skewing and improve neurological recovery.